Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the problem, follow these steps:
Step 1: Understand the given functional equation.
We are given:
[tex]\[ f(3x - 5) = 15x + 8 \][/tex]
Step 2: Introduce a substitution to simplify the expression.
Let [tex]\( u = 3x - 5 \)[/tex].
Step 3: Rewrite the given equation using [tex]\( u \)[/tex].
Since [tex]\( u = 3x - 5 \)[/tex], we can solve for [tex]\( x \)[/tex] in terms of [tex]\( u \)[/tex]:
[tex]\[ x = \frac{u + 5}{3} \][/tex]
Step 4: Express [tex]\( f(u) \)[/tex] using this substitution.
Replace [tex]\( x \)[/tex] in [tex]\( 15x + 8 \)[/tex]:
[tex]\[ f(u) = 15 \left(\frac{u + 5}{3}\right) + 8 \][/tex]
Step 5: Simplify the expression for [tex]\( f(u) \)[/tex].
First, distribute the 15:
[tex]\[ f(u) = 15 \cdot \frac{u + 5}{3} + 8 \][/tex]
[tex]\[ f(u) = 5(u + 5) + 8 \][/tex]
Next, distribute the 5:
[tex]\[ f(u) = 5u + 25 + 8 \][/tex]
Combine like terms:
[tex]\[ f(u) = 5u + 33 \][/tex]
Step 6: Replace [tex]\( u \)[/tex] back with [tex]\( x \)[/tex].
Since [tex]\( u = x \)[/tex] in the function [tex]\( f(u) \)[/tex], we have:
[tex]\[ f(x) = 5x + 33 \][/tex]
Step 7: Calculate [tex]\( f(2) \)[/tex].
Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 5(2) + 33 \][/tex]
[tex]\[ f(2) = 10 + 33 \][/tex]
[tex]\[ f(2) = 43 \][/tex]
Final Results:
- The function [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = 5x + 33 \][/tex]
- The value of [tex]\( f(2) \)[/tex] is:
[tex]\[ f(2) = 43 \][/tex]
Step 1: Understand the given functional equation.
We are given:
[tex]\[ f(3x - 5) = 15x + 8 \][/tex]
Step 2: Introduce a substitution to simplify the expression.
Let [tex]\( u = 3x - 5 \)[/tex].
Step 3: Rewrite the given equation using [tex]\( u \)[/tex].
Since [tex]\( u = 3x - 5 \)[/tex], we can solve for [tex]\( x \)[/tex] in terms of [tex]\( u \)[/tex]:
[tex]\[ x = \frac{u + 5}{3} \][/tex]
Step 4: Express [tex]\( f(u) \)[/tex] using this substitution.
Replace [tex]\( x \)[/tex] in [tex]\( 15x + 8 \)[/tex]:
[tex]\[ f(u) = 15 \left(\frac{u + 5}{3}\right) + 8 \][/tex]
Step 5: Simplify the expression for [tex]\( f(u) \)[/tex].
First, distribute the 15:
[tex]\[ f(u) = 15 \cdot \frac{u + 5}{3} + 8 \][/tex]
[tex]\[ f(u) = 5(u + 5) + 8 \][/tex]
Next, distribute the 5:
[tex]\[ f(u) = 5u + 25 + 8 \][/tex]
Combine like terms:
[tex]\[ f(u) = 5u + 33 \][/tex]
Step 6: Replace [tex]\( u \)[/tex] back with [tex]\( x \)[/tex].
Since [tex]\( u = x \)[/tex] in the function [tex]\( f(u) \)[/tex], we have:
[tex]\[ f(x) = 5x + 33 \][/tex]
Step 7: Calculate [tex]\( f(2) \)[/tex].
Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 5(2) + 33 \][/tex]
[tex]\[ f(2) = 10 + 33 \][/tex]
[tex]\[ f(2) = 43 \][/tex]
Final Results:
- The function [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = 5x + 33 \][/tex]
- The value of [tex]\( f(2) \)[/tex] is:
[tex]\[ f(2) = 43 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.